Penguatan Daya Saing UMKM melalui Optimalisasi Kemasan Produk dan Pemasaran Digital di Kabupaten Gowa - Ilma Wulansari Hasdiansa; Sitti Hasbiah; Annisa Paramaswary Aslam; Nurul Fadilah Aswar; Ahmad Farhan (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in supporting the community’s economy; however, they still face various limitations in business management, particularly in product packaging and digital marketing. This community service activity aims to enhance the capacity of MSME actors in optimizing product packaging design and utilizing digital marketing in Pattallassang District, Gowa Regency. The activity was conducted in February 2026 and involved 8 home-based business actors as participants. The methods used included socialization, training, and participatory-based mentoring, which began with a pre-test to measure the participants’ initial level of understanding. The materials provided covered product packaging design, label or logo creation, and the use of social media and marketplaces in digital marketing. The results showed an improvement in participants’ knowledge and skills in designing more attractive product packaging and utilizing digital platforms as marketing tools. Participants also began to understand the importance of branding and marketing strategies in increasing product competitiveness. Overall, this activity had a positive impact on improving the capacity of MSME actors in terms of knowledge, skills, and attitudes in managing their businesses. This activity is expected to be an initial step in encouraging MSME actors to be more adaptive to technological developments and able to compete in a broader market.